Understanding Literature through Dichotomous Frame - Tumbahang, Mohan Kumar (JODEM: Journal of Language and Literature, 2023)
This article aims at dealing with the issue of ’dichotomies in literature’, though it is not explicitly referred to in the literary genres. The specific objective of this study is to explore the dichotomous aspects in the literary field and thereby to assess how the knowledge of two-fold distinctions helps the readers understand the whole issue of certain aspect of mutually exclusive points. While dealing with the notion ’dichotomy in literature’, it has availed the qualitative research design which has primarily relied on non-numerical data with explicit reference to the binary oppositions, concepts, definition and the features. The necessary data have been drawn from authentic books, journals or online resources. The available data have been analyzed by applying the compare-contrast pattern of development. From the analysis, the conclusion has been drawn that in the literary discourse, there are significant numbers of dichotomous notions, and when they are dealt with the two-fold distinctions, the mutually exclusive entities can be grasped more easily than treating them in isolation. It is fairly expected that the study can be helpful for the beginners of the literary studies.